Nonalcoholic steatohepatitis is the most common indication for liver transplantation among the elderly: Data from the United States Scientific Registry of Transplant Recipients. Issue 7 (28th February 2022) - Stepanova, Maria; Kabbara, Khaled; Mohess, Denise; Verma, Manisha; Roche‐Green, Alva; AlQahtani, Saleh; Ong, Janus; Burra, Patrizia; Younossi, Zobair M.
Abstract: As the US population ages, more elderly patients may need liver transplantation. Our aim was to assess recent trends among elderly individuals requiring liver transplant in the United States. Scientific Registry of Transplant Recipients data (2002–2020) were used to select elderly (≥65 years) liver transplant candidates and assess on‐list and posttransplant outcomes. During the study period, 31, 209 liver transplant candidates ≥65 years were wait listed. Common etiologies included nonalcoholic steatohepatitis (NASH; 31%), hepatitis C (23%), and alcoholic liver disease (18%); 30% also had hepatocellular carcinoma (HCC). Over time, the proportion of patients ≥65 years among all adult liver transplant candidates increased from 9% (2002–2005) to 23% (2018–2020) (trend, p < 0.0001). The proportion of NASH among elderly candidates increased from 13% (2002–2005) to 39% (2018–2020). Of the elderly candidates, 54% eventually received transplants. In multivariate analysis, independent predictors of a higher chance of receiving a transplant for the elderly included more recent years of listing, male sex, higher Model for End‐Stage Liver Disease (MELD) score, and HCC (all p < 0.01). Posttransplant mortality in elderly transplant recipients was higher than in younger patients but continued to decrease over time. In multivariate analysis, independent predictors of higher posttransplant mortality for elderly transplant recipients were earlier years of transplantation, older age, male sex, higher MELD score, history of diabetes, retransplantation, and having HCC (all p < 0.01). The proportion of elderly patients in need of liver transplantation in the United States is sharply increasing. NASH is the most common indication for liver transplantation among the elderly. The outcomes of these patients have been improving in the past 2 decades. Abstract : As the U.S. population ages, more elderly patients may need liver transplantation. In this study of a national registry for transplant recipients, we found that in 2020 nonalcoholic steatohepatitis (NASH) was the most common indication for liver transplantation among Americans 65 years of age or older. We have also shown that the outcomes of elderly patients in need of a liver transplant, including the rate of transplantation and post‐transplant mortality, have improved over the past two decades.image